PERBANDINGAN EFEKTIVITAS POVIDONE IODINE DENGAN KOPI ROBUSTA TERHADAP PENYEMBUHAN LUKA SAYAT PADA MENCIT (MUS MUSCULUS) - RAHU ALPHAMA; ERY SUHAYMI (LP2MTBM MAKARIOZ, 2021)
Wound healing is a vital procces. Therefore it should be treat carefully which cause the wound to healing well. There areseveral ways to precipitate the wound healing whether is systemic or local. Unify the edges of the wound could be done bysuturing. The small wound could be heal by it self without any infection. Coffe seeds countain chlorogenic acid. Chlorogenicacid have some important benefits such as antioxidant, antibacterial, and also can precipitate the wound healing. Coffeseeds could be used in the wound which cause it to dry faster and not cause any inflammation. To compare the effectivity ofwound healing using robusta coffe seeds and povidone iodine in wound incised healing in mus musculus. This study uses anexperimental method that is designing a post test with a design control group to compare wound utilization using robustacoffee and povidone iodine to the treatment of incision in mice. The average speed of wound healing, coffee had the fastesttime of 6.56 days followed by povidone iodine 10.56 days, while controls were 11.67 days. In terms of effectiveness, Robustacoffee is more effective than controls, namely 8.4: 8. Povidone iodine is no more effective than control ie 8: 8 and after thesignificance test the results are not significant. Differences in the effect of administration of robusta coffee with povidoneiodine in the recovery of incised wounds in mice (Mus musculus). Robusta coffee powder can be overcome as an alternativewhen wound recovery.